Corporate Liability On Copyright - Melia Septiana Ketaren (Universitas Ahmad Dahlan, 2018)
Corporate crime in the field of copyright continues to grow following the economic development of a nationâ€™s society. Therefore, the application of criminal law, starting from prevention efforts through administrative legislation, criminalization, and law enforcement efforts, must always receive serious attention. Copyright is an exclusive right for the creator or recipient of the right to announce and/or reproduce his creation or give permission for it by not reducing restrictions according to the applicable laws and regulations. The granting of criminal sanctions to corporate administrators who commit copyright crimes will not give deterrent effects to the corporation, because the loss of one and/or several employees who undergo criminal sanctions can be easily replaced by anyone and at any time. The method used in this study is Normative Jurisdiction. The results of the study show that corporations in copyright infringement must be prosecuted criminally, because the losses are very large, have multi-dimensional consequences, ranging from losses to the state, the wider community of owners or copyright holders, and create frustration that weakens the spirit of creativity.Â Kata Kunci: Pertanggungjawaban Korporasi, Hak Cipta.Â